Development of a qPCR Strategy to Select Bean Genes Involved in Plant Defense Response and Regulated by the Trichoderma velutinum – Rhizoctonia solani Interaction - Mayo, Sara; Cominelli, Eleonora; Sparvoli, Francesca; González-López, Oscar; Rodríguez-González, Alvaro; Gutiérrez, Santiago; Casquero, Pedro A. (Frontiers in Plant Science, 2016)
Bean production is affected by a wide diversity of fungal pathogens, among them Rhizoctonia solani is one of the most important. A strategy to control bean infectious diseases, mainly those caused by fungi, is based on the use of biocontrol agents (BCAs) that can reduce the negative effects of plant pathogens and also can promote positive responses in the plant. Trichoderma is a fungal genus that is able to induce the expression of genes involved in plant defense response and also to promote plant growth, root development and nutrient uptake. In this article, a strategy that combines in silico analysis and real time PCR to detect additional bean defense-related genes, regulated by the presence of Trichoderma velutinum and/or R. solani has been applied. Based in this strategy, from the 48 bean genes initially analyzed, 14 were selected, and only WRKY33, CH5b and hGS showed an up-regulatory response in the presence of T. velutinum. The other genes were or not affected (OSM34) or down-regulated by the presence of this fungus. R. solani infection resulted in a down-regulation of most of the genes analyzed, except PR1, OSM34 and CNGC2 that were not affected, and the presence of both, T. velutinum and R. solani, up-regulates hGS and down-regulates all the other genes analyzed, except CH5b which was not significantly affected. As conclusion, the strategy described in the present work has been shown to be effective to detect genes involved in plant defense, which respond to the presence of a BCA or to a pathogen and also to the presence of both. The selected genes show significant homology with previously described plant defense genes and they are expressed in bean leaves of plants treated with T. velutinum and/or infected with R. solani.